2004
DOI: 10.1017/s0954579404044566
|View full text |Cite
|
Sign up to set email alerts
|

Children's emotion processing: Relations to emotionality and aggression

Abstract: We examined the relations between emotionality, emotion processing, and aggression in 182 first-and second-grade children. Consistent with Tomkins' and Izard's theoretical predictions, emotionality correlated with emotion processing. In particular, the happiness component of emotionality correlated with emotion attribution accuracy and empathy, the anger component correlated with anger attribution bias and empathy, and the fear component correlated with fear attribution bias. Multiple emotion processing defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
196
3
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(214 citation statements)
references
References 77 publications
6
196
3
9
Order By: Relevance
“…A bias toward anger reported in primary-school-aged children with externalizing or internalizing symptoms was not evident in this study (Richards et al, 2007;Schultz et al, 2004). Previous studies in children with conduct and internalizing difficulties have utilized tasks measuring children's hostile attribution in ambiguous situations.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…A bias toward anger reported in primary-school-aged children with externalizing or internalizing symptoms was not evident in this study (Richards et al, 2007;Schultz et al, 2004). Previous studies in children with conduct and internalizing difficulties have utilized tasks measuring children's hostile attribution in ambiguous situations.…”
Section: Discussioncontrasting
confidence: 51%
“…Increased symptoms of hyperactivity in 6 to 12-year-old children, for example, have been linked to difficulties recognizing both positive (happy) and negative (anger, sadness, fear) facial expressions of emotion (Boakes, Chapman, Houghton, & West, 2008;Corbett & Glidden, 2000;Pelc, Kornreich, Foisy, & Dan, 2006;Sinzig, Morsch, & Lehmkuhl, 2008). In addition, children and adolescents with conduct problems showed increased errors detecting negative (sad, angry, and fearful) facial expressions (Blair, Colledge, Murray, & Mitchell, 2001;Fairchild, Stobbe, Van Goozen, Calder, & Goodyer, 2010) and a hostility bias-a tendency to attribute anger to facial expressions of emotion (Dodge, Bates, & Pettit, 1990;Schultz, Izard, & Bear, 2004). Further research has found that elevated anxiety symptoms in children aged 10-11 years were also linked to increased attributions of anger to facial expressions with low-intensity happiness (Richards, French, Nash, Hadwin, & Donnelly, 2007).…”
mentioning
confidence: 99%
“…Similarly, CE and NLEs did not mediate the link between temperamental anger/frustration (parents' reports) and externalizing. Anger/frustration might have more a direct relation to externalizing than authoritarian parenting; alternatively, other processes might mediate the anger/frustration -externalizing association (e.g., emotion attribution and empathy; Schultz, Izard, & Bear, 2004). …”
Section: Nles and Ce As Mediators Of The Parenting-and Temperament-exmentioning
confidence: 99%
“…Many protective factors that are hypothesized to promote social competence are also thought to inoculate children from developing externalizing behavior problems. Although the research literature on protective factors that relate to risk has been slow in developing, evidence suggests that socially adaptive interpersonal problem-solving (Wentzel 1991), empathy (Schultz, Izard, and Bear 2004), and parental use of positive rewards and encouragement to support appropriate behavior (Gorman-Smith et al 2000) are related to a lower occurrence of problem behaviors, such as aggression and delinquency.…”
Section: Social Development and Risk Preventionmentioning
confidence: 99%